Poultry rearing on perforated plastic floors and the effect on air quality, growth performance, and carcass injuries - Experiment 2: Heat stress situation - Almeida, E. A. [UNESP]; Sant'Anna, A. C.; Crowe, T. G.; Macari, M. [UNESP]; Furlan, R. L. [UNESP] (Oxford Univ Press, 2018)
Previously, we reported the effect of rearing conditions (plastic floors and air quality) on carcass injury development of broiler chickens at thermal comfort. In this study, the same rearing conditions were tested at thermal stress. The birds were reared in 2 climatic chambers, and the experiment followed a completely randomized design with one factor, flooring material: wood shaving or perforated plastic. The birds were divided into 16 experimental pens, being 8 females and 8 males. The studied parameters were the same as the previous study (ammonia concentration, carbon dioxide, performance, carcass yield, and variability, and scores of hygiene, gait and chest, and hocks and footpad lesions). Higher ammonia (15 ppm vs. 4 ppm) and carbon dioxide (1,000 ppm vs. 850 ppm) concentration was seen at d 42 for the wood shavings floor as compared to the perforated plastic floor, respectively. Regarding gender, males had better performance than females at 42 d of age on both floor types. Males reared on wood shavings showed a higher meat production (29.049 kg/m(2)) than females (24.700 kg/m(2)). There were observed breast lesion incidences of 10.4% (score 1) in males reared on the plastic floor, as well higher incidence of hock injury and footpad dermatitis. Chickens reared on plastic flooring showed better hygiene than chickens reared on wood shavings. Our findings revealed that the use of perforated plastic flooring in a heat stress situation can improve the air quality (less CO2 and NH3 concentration) and bird cleanliness. On the other hand, chickens are more susceptible to develop lesions in the breast, hock, and footpad. We conclude that the use of plastic flooring in heat stress conditions needs more attention, since chickens are more susceptible to develop lesions on the carcass, being a source of pain, impairing bird wellbeing and causing losses in meat production.
Keywords: plastic floor; ammonia concentration; carcass injury; poultry litter; animal welfare